THE IMPACT OF RECRUITMENT SYSTEM AND CAREER DEVELOPMENT ON THE ENHANCING OF EFFECTIVENESS IN WORKING THROUGH COMPENSATION AS INTERVENING VARIABLE AT NIAGARA HOTEL PARAPAT - Elisabet Siahaan; Parapat Gultom (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
Lake Toba is the biggest and deepest volcanic lake in South-East Asia, located in Parapat, Simalungun Regency, North Sumatra Province, Indonesia. It is the tourism icon in Indonesia andrecommended to be one of the Global Geopark Network (GGN) tourism icons established by UNESCO. The tourists visiting this destination are still as not many as other tourism destinations in Indonesia. Many factors cause such condition. Hotel’s hospitality service, which is an important role for tourism convenience, is not at its maximum quality. Therefore, the domestic and foreign tourists have not been able to thoroughly enjoy the beauty of Lake Toba. The low quality of services may be caused by the less effective of the recruitment system, career development, and compensation systems which result in the diseffectiveness of employees work. The purpose of this research is to analyze the impact of how recruitment system and career development on the enhancing of effectiveness in working through compensation as the intervening variable. The research is carried out at Niagara Hotel Parapat. The population of this study is 174 Niagara Hotel Parapat’s employees and 64 of them are selected as samples for this research. The method used in this research is Path Analysis. The result shows that recruitment system and career development (test-F) have significant positive influence over compensation. There is a significant positive influence between recruitment over compensation, but there is no significant influence between the career developments toward compensation. It causes career development possibility at Niagara Hotel to be too short and the compensation system to still be under the province minimum wage. Recruitment system, career development, and compensation affect positively and significantly to the effectiveness in working. There are significant positive influences among recruitment system, career development, and compensation with respect to the effectiveness of the employees work at Niagara Hotel Parapat. Recruitment is a dominant variable which influences more to work effectiveness rather than to career development, directly or indirectly through compensation. The research also shows that compensation is an intervening variable for recruitment system but not for career development.Danau toba merupakan danau vulkanik terbesar dan terdalam di Asia Tenggara yang terletak di Parapat, Kabupaten Simalungun, Provinsi Sumatera Utara, Indonesia. Danau toba adalah salah satu ikon pariwisata di Indonesia dan disarankan untuk menjadi satu ikon pariwisata global geopark network (GGN ) yang didirikan oleh UNESCO. Namun demikian layanan perhotelan, yang berperan penting bagi kenyamanan wisatawan belum dilakukan secara maksimal. Karena itu, para wisatawan dalam dan luar negeri belum sepenuhnya menikmati keindahan Danau Toba karena tidak didukung oleh akomodasi fasilitas yang disebabkan oleh keterbatasan sumber daya manusia. Ini disebabkan oleh kurang efektif sistem perekrutan, pengembangan karir, dan sistem kompensasi yang berdampak pada ketidakefektivan kerja para karyawan. Tujuan penelitian ini adalah untuk menganalisa dampak dari sistem perekrutan, pengembangan karir, terhadap efektivitas kerja dengan kompensasi sebagai variabel perantara. Penelitian dilakukan di Niagara Hotel Parapat. Populasi sebanyak 174 karyawan dan 64 orang karyawan sampel. Metode analisis data adalah analisis jalur. Hasilnya menunjukkan bahwa sistem perekrutan dan pengembangan karir secara bersama-sama (Uji-F) memiliki pengaruh positif signifikan terhadap kompensasi. Berdasarkan uji parsial (Uji-t) bahwa sistem perekrutan berpengaruh positif signifikan terhadap kompensasi, akan tetapi pengembangan karir tidak berpengaruh signifikan terhadap kompensasi. Hal ini disebabkan karena pengembangan karir di Niagara Hotel masih terlalu pendek dan sistem kompensasi masih di bawah standar upah minimum provinsi. Secara langsung sistem perekrutan, pengembangan karir, dan kompensasi berpengaruh positifsignifikan terhadap efektivitas kerja. Perekrutan merupakan variabel yang dominan mempengaruhi efektivitas kerja dibandingkan jenjang karir, baik langsung maupun tidak langsung melalui kompensasi. Penelitian ini juga menunjukkan bahwa kompensasi merupakan variabel perantara antara perekrutan terhadap efektivitas kerja, sedangkan kompensasi tidak mampu menjadi variabel perantara antara pengembangan karir terhadap efektivitas kerja.